ANALISA KANDUNGAN TOTAL ZAT PADAT TERSUSPENSI (TSS) PADA MUARA SUNGAI DI TELUK MANADO - Tarumingkeng, Adrie (Sam Ratulangi University, 2010)
ABSTRACTTarumingkeng, A. and W. Patty. 2010. Analysis of Total solid suspended at river downstream Manado bay.A research was done to analyze total solid suspended at downstream river, Manado bay. Total solid suspended content was analyzed in nine stations at Malalayang river stream. Total solid suspensions and turbidity of water were analyzed using Horiba U-10. The result shows that the highest total solid suspensions were in station 1, 4 and 7. High total solid suspensions caused by its position near to the land. Total solid suspensions Malalayang river have uncertain trend. Turbidity influence to total solid suspended of Malalayang river.Kata kunci : total solid suspended, turbidity, river, Malalayang